(untitled) (Research, Society and Development, 2024)
The objective of the study is to compile the most recent evidence on the influence of breathing techniques on sports performance, carrying out a narrative review of the literature through the VHL (Virtual Health Library) and PubMed databases, including articles published between 2019 and 2024 in Portuguese and English. 10 studies were selected that showed that both Inspiratory Muscle Training (IMT) and other respiratory techniques, such as diaphragmatic breathing, controlled breathing and rhythmic breathing, were efficient in improving sports performance and respiratory function. IMT increases the strength and resistance of the inspiratory muscles, improving lung ventilation and respiratory efficiency. Additionally, other breathing techniques help reduce fatigue, improve muscle oxygenation, and control anxiety during intense exercise. It is concluded that IMT is effective in improving respiratory function and athletic performance, but the combination with other respiratory techniques provides a more complete and effective approach. More research is needed to explore the underlying mechanisms and optimize training protocols for different groups of athletes, maximizing respiratory and athletic benefits.